Nutritional impacts on gastroesophageal reflux disease: an integrative review - Navarro, Laís Nanci Pereira (2023)
Gastroesophageal Reflux Disease (GERD) has a multifactorial cause and is characterized by the consequence of the return of stomach contents and the presence of symptoms such as regurgitation, cough and phlegm, which directly triggered the quality of life of the individual treated with this pathology. Some of these symptoms are aggravated or relieved after consuming certain foods. The objective of this study is to analyze how nutrition can interfere with the symptoms of GERD. This is an integrative literature review based on the search for articles in the BVS/BIREME (Virtual Health Library), PubMed and SciELO (Scientific Electronic Library Online) databases, where 154 articles were identified, of which 11 articles were selected for this review. Among these studies, improvements in GERD symptoms were observed after application of the Mediterranean diet and a gluten-free diet (for celiacs). On the other hand, the symptomatology was aggravated after the ingestion of simple carbohydrates, meals with a high glycemic load, consumed foods and citrus and part of the diet rich in FODMAP (Fermentable Oligosaccharides, Disaccharides, Monosaccharides and Polyols). It is concluded that food in individuals influenced by GERD is an important factor for the improvement of symptoms and that some foods aggravate the situation.